Realising Inclusive Physical Education: Barriers and Strategies for Including Students with Disabilities - Novri Gazali; Merlina Sari; Edi Setiawan; Ahmad Rahmadani; Feby Elra Perdima; Nagoor Meera Abdullah; Jet Longakit (Journal of Sport Science and Education, 2025)
Inclusive physical education still faces challenges in practice in regular schools. This study aimed to identify the main barriers and effective strategies in its implementation. Researchers selected a total of 245 physical education teachers from various school levels in Pekanbaru, Indonesia, using purposive sampling based on their experience teaching students with disabilities. Validated for the Indonesian setting, the PEATID III (Physical Educators' Attitudes Towards Teaching Individuals with Disabilities III) questionnaire was used for data collecting with great dependability (α = 0.88). According to results, 68% of teachers reported exclusive attitudes from non-disabled students, 59% had never attended inclusion training, and 68% encountered limits of disability-unfriendly facilities. Implementation of inclusive strategies—such as curriculum customisation, the use of assistive technology, and parent collaboration—strongly connected teachers' favourable opinions with This study validates the need for synergy among instructors' pedagogical preparedness, easily available infrastructure, and school and family social support to provide fair and significant physical learning. The findings of this study significantly help Indonesia's inclusive physical education policies and practices to be developed.